Relationship between total quality management (TQM) practises and operational performance in manufacturing company - Nur Anis, Buniamin (2016)
Total quality management (TQM) practises are well known approaches that most of the overseas company used. But in Malaysian company, this approach is not so often used. Other than that, not many researchers do the research about the effect of TQM practises on operational performance. So the aims of this research are to identify the levels of TQM practises (leadership, customer focus, management of people, process improvement, strategic planning and use of information and analysis) for operational performance and to determine the effect of TQM practises on operational performance. The indicators of operational performance are productivity, quality and waste level. The collected data was analysed by using descriptive statistic, reliability, normality, Pearson Correlation, single mean t-test and regression analysis. As a result, only strategic planning and process improvement practises positively contribute to operational performance. For future researcher, they should do more research about operational performance like increase the numbers of indicators for operational performance. Therefore, they can give more comprehensive understanding to colleagues and students about operational performance.